Growth and metabolic disorders in chronic paediatric diseases : St. John's College, Cambridge, UK, December 10-11, 2001 - Czernichow, Paul; Dunger, D. B; Savage, M. O (Karger, 2002)
Presenting papers on growth and metabolic disorders from December 2001, this volume covers aspects of Crohn\'s disease, coeliac disease, cystic fibrosis, growth failure and contributary factors, bone structure, diabetes, arthritus, growth hormones and steroids in children.
Hormone research, ISSN 0301-0163 vol. 58, suppl. 1, September 2002
Keywords: Chronic Disease; metabolické nemoci; endokrinologie; Metabolic Diseases; vnitřní lékařství; Growth Disorders; dítě; pediatrie; Child; poruchy růstu; chronická nemoc